2018
DOI: 10.1515/ntrev-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

Social media buzz created by #nanotechnology: insights from Twitter analytics

Abstract: The word “nanotechnology” has been exaggerated not only by media but also by scientist groups who have overstated the unforeseen benefits of nanotechnology to validate research funding. Even ecologists, who normally remain indulged in doom-and-gloom divinations, use this word to fuel their own motives. Such outcomes lead to widespread misinformation and an unaware public. This research work is a staunch effort to filter the Twitter-based public opinions related to this word. Our results clearly indicate more o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…With a similar approach, Singh et al found that there are many positive sentiments associated with the subject nanotechnology, such as trust in the technology, anticipation about the outcome, and joy about the availability of the predicted applications, which far outweigh the anger associated with nanowaste, mistrust about failures to meet targets, and anger associated with wasting tons of taxpayers' money on nanotechnology projects. 61 …”
Section: Discussionmentioning
confidence: 99%
“…With a similar approach, Singh et al found that there are many positive sentiments associated with the subject nanotechnology, such as trust in the technology, anticipation about the outcome, and joy about the availability of the predicted applications, which far outweigh the anger associated with nanowaste, mistrust about failures to meet targets, and anger associated with wasting tons of taxpayers' money on nanotechnology projects. 61 …”
Section: Discussionmentioning
confidence: 99%
“… Data Collection: The collection of data always remains the most crucial part of any research as it forms the fundamental of a sustained foundation of the entire research work (Stieglitz et al, 2018 , 2020 ; Singh et al, 2018a ). Hence, Twitter API was integrated into the R-language script to retrieve data (tweets) from Twitter in an authenticated manner.…”
Section: Methodsmentioning
confidence: 99%
“…al., 2018a). The descriptive analysis gives descriptive statistics about number of tweets, number of tweet senders, hashtags, @mentions, word cloud etc (Chae, 2015;Ganis and Kohirkar, 2015;Purohit et al, 2013;Singh et al, 2018b).…”
Section: Endmentioning
confidence: 99%